Optimizing Resources of an FPGA-based Smart Camera Architecture - Azman, Amelia Wong; Bigdeli, Abbas; Mohd Mustafah, Yasir; Lovell, Brian (2007)
The acceptance of reconfigurable platforms specifically FPGAs in embedded system design is becoming more apparent. While there are varieties of platforms available for smart camera implementation, our interest is mainly on reconfigurable platforms, specifically FPGAs. In this paper we discuss the research opportunity and the importance of hardware/software partitioning on FPGA-based smart camera platform. An overview of our current research work on the above mentioned problem is describe in this paper.